The Role of Aquatourism in Sustaining Maine’s Working Waterfronts - Paras, Caroline; Michaud, Tracy (Maine Policy Review, 2023)
Maine tourism relies heavily on the iconic imagery of working waterfronts, including harbors bobbing with lobster boats surrounded by shingled shacks in a rainbow of buoys. Adapted from agritourism, aquatourism is an experience that engages visitors with the landscape and stories of those who fish. According to the literature on the Experience Economy, the emotions generated by such experiences can translate into sales in real time as well as behavioral intentions to purchase in the future. What role can aquatourism play in sustaining working waterfronts? Using a mixed methods approach, this research study utilizes interviews from both producers and consumers to understand the value that aquatourism can generate for the Maine fishing industry. This research shows that with a design that incorporates Participation, People, Product, and Place, the fishing industry and its partners can engage visitors in memorable experiences that could transform them into loyal consumers of Maine fishery products.
Keywords: Aquatourism; agritourism; working waterfront; brand; authenticity